FI-ICP-TOFMS for quantification of biologically essential trace elements in cerebrospinal fluid – high-throughput at low sample volume. Issue 15 (1st July 2019) - Theiner, Sarah; Schoeberl, Anna; Fischer, Lisa; Neumayer, Sophie; Hann, Stephan; Koellensperger, Gunda
Abstract : A high-throughput ICP-TOFMS method is presented for multi-element quantification in CSF material requiring low sample volume. Abstract : In this work, we introduce a high-throughput quantitative multi-element method for biological fluids enabled by omitting sample preparation and an analysis time of a few seconds per sample. For the first time, flow injection of an undiluted cerebrospinal fluid (CSF) was combined to state-of-the-art ICP-TOFMS detection for multi-element analysis. Owing to the low sample volume and trace element concentrations of the CSF, flow injection methods with only 5 μL sample intake were used in combination with an icp TOF 2R TOF-based ICP-MS instrument. Due to the lack of certified reference materials for CSF analysis, a validated method employing open vessel digestion of the CSF material in combination with ICP-sectorfield-MS analysis was carried out and used as a reference. Additionally, the performance of the flow injection ICP-TOFMS was cross-validated by flow injection quadrupole-based ICP-MS/MS analysis using both external calibration and isotope dilution strategies. In the latter case, the sample had to be injected several times because of the need for tailored gas conditions for different elements. Overall, flow injection of biological fluids delivered quantitative values, which were in excellent agreement with the gold standard established by ICP-SFMS demonstrating the capability of ICP-TOFMS analysis in terms of resolution and sensitivity for the accurate quantification of trace elements in biological samples.